In debt we trust America before the buble bursts - Schechter, Danny (United states : Media Education Foundation, 2007)
A documentary examining the increasing debt burden carried by millions of Americans argues that corrupt practices by financial and government institutions are fostering citizens' dependence on credit while creating a ballooning national debt that is leading the country towards fiscal disaster
Special features include: Trailer, interviews with Danny Schechter, Steven Green, and Lorraine Bracco
Title from title screen
Director of photography, Gary Keith Griffin ; editor, Linda Hattendorf ; music supervision, Polar Levine ; written, produced, and directed by Danny Schechter
In English with English subtitles
Keywords: Debt -- United States; Debts, Public -- United States; Economic stabilization -- United States; Consumer credit -- United States; Finance, Personal -- United States